A large region within the Rous sarcoma virus matrix protein is dispensable for budding and infectivity. - Nelle, T D (1996)
All retroviruses have a layer of matrix protein (MA) situated directly beneath the lipid of their envelope. This protein is initially expressed as the amino-terminal sequence of the Gag polyprotein, where it plays an important role in binding Gag to the plasma membrane during the early steps of the budding process. Others have suggested that MA may provide additional functions during virion assembly, including the selective incorporation of viral glycoproteins and the RNA genome into the emerging virion. To further study the role of the Rous sarcoma virus MA sequence in the viral replication cycle, we have pursued an extensive deletion analysis. Surprisingly, the entire second half of MA (residues 87 to 155) and part of the neighboring p2 sequence were found to be dispensable not only for budding but also for infectivity in avian cells. Thus, all of the functions associated with the Rous sarcoma virus MA sequence must be contained within its first half.